2011
DOI: 10.1371/journal.pone.0023279
|View full text |Cite
|
Sign up to set email alerts
|

BAAV Mediated GJB2 Gene Transfer Restores Gap Junction Coupling in Cochlear Organotypic Cultures from Deaf Cx26Sox10Cre Mice

Abstract: The deafness locus DFNB1 contains GJB2, the gene encoding connexin26 and GJB6, encoding connexin30, which appear to be coordinately regulated in the inner ear. In this work, we investigated the expression and function of connexin26 and connexin30 from postnatal day 5 to adult age in double transgenic Cx26Sox10Cre mice, which we obtained by crossing connexin26 floxed mice with a deleter Sox10–Cre line. Cx26Sox10Cre mice presented with complete connexin26 ablation in the epithelial gap junction network of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 47 publications
5
89
0
Order By: Relevance
“…However, skin or buccal biopsies of these patients have revealed that not only Cx30 but also Cx26 expression was dramatically reduced, demonstrating that both genes are coregulated and suggesting the existence of a common cis-regulatory element in the DFNB1 locus (Common et al, 2005;Rodriguez-Paris and Schrijver, 2009). A comparable situation is found in mouse, in which Cx30 inactivation causes profound deafness (Teubner et al, 2003;Cohen-Salmon et al, 2007;Sun et al, 2009), but also strongly reduces the expression of Cx26 (Ortolano et al, 2008;Lynn et al, 2011). Thus, how exactly the lack of Cx30 translates into a deafness phenotype still remains unclear.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, skin or buccal biopsies of these patients have revealed that not only Cx30 but also Cx26 expression was dramatically reduced, demonstrating that both genes are coregulated and suggesting the existence of a common cis-regulatory element in the DFNB1 locus (Common et al, 2005;Rodriguez-Paris and Schrijver, 2009). A comparable situation is found in mouse, in which Cx30 inactivation causes profound deafness (Teubner et al, 2003;Cohen-Salmon et al, 2007;Sun et al, 2009), but also strongly reduces the expression of Cx26 (Ortolano et al, 2008;Lynn et al, 2011). Thus, how exactly the lack of Cx30 translates into a deafness phenotype still remains unclear.…”
Section: Introductionmentioning
confidence: 72%
“…3). Thus, micromechanics and transduction, the two basic functions underpinning normal hearing (Ashmore and Gale, 2000) are maintained without Cx30, provided that the Cx30 coding exon is deleted without introducing other perturbation of the surrounding sequences. Accordingly, the simple insertion of Hyg gene into the 3Ј end of Cx30 in Cx30 fl/fl mice decreased the expression of both Cx30 and Cx26 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Note that normal auditory thresholds were reported for adult Cx30 +/− mice (30), whereas both Cx30 −/− mice (21, 30) and mice with targeted ablation of Cx26 in the inner ear (31,32) are profoundly deaf at all tested frequencies. We also showed that whole-cochlea samples from postnatal Cx30 −/− mice have only ∼8% residual Cx26 mRNA (27).…”
Section: Hearing Loss In Pipkiγmentioning
confidence: 81%
“…The severe hearing loss of Cx30 −/− mice (30) and of mice with targeted ablation of Cx26 in the inner ear (31,32) is associated with substantial cell death affecting hair cells and supporting cells. By contrast, we did not detect morphological abnormalities in the inner ear of adult PIPKIγ +/− mice, in which hair cells, spiral ganglion neurons and nerve fiber counts were indistinguishable from WT controls (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the endocochlear potential remains below 15 mV between P1 and P5 and increases rapidly after P7, reaching levels of 80-100 mV around P16 (38). In adult mice, we measured endocochlear potentials as large as 117 mV (62). In adult nonsensory cells of the rodent organ of Corti, the cell resting potential can be as negative as −90 mV (63); therefore the ΔV m across their apical plasma membrane can exceed −200 mV (inside minus outside).…”
Section: Discussionmentioning
confidence: 98%